Literatura Brasileira entre a tradição e a ruptura: um olhar sobre as relações de gênero, sexualidades e representações do feminino - Faria, Daniele Ribeiro de (2016)
In this dissertation, I intended to investigate, through the selection of three Brazilian novels - Senhora (1875), by José de Alencar; Gabriela cravo e canela: crônicas de uma cidade do interior (1958), by Jorge Amado; As Meninas (1973), by Lygia Fagundes Telles - how gender relations and representations of the feminine are constructed into Brazilian literary narratives. I also intended to analyze the relations of power observed in literary discourse and involving productions of knowledge and truths. In making an analysis of various commentaries on the novels listed, I searched to perceive as rules of formation or as conditions of possibility of statements, as regimes of truth are formed in a certain society and how legitimate discourses are reproduced and transmitted. The critical perspective that I proposed to make transited between the text and the context, seeking as temporal and spatial specificities within which the romances were constructed, as well as the establishment of relations with other discourses of other times and places, always in this movement to realize the keep and the discontinuities in gender representations. Therefore, my studies were carried out under the focus of Cultural Studies and Gender Studies linked to the post-structuralist aspect of analysis. Within the theoretical perspectives, the rigidity, the essences, the absolute thought, the truths considered as universal, totalizing and immutable are questioned all the time, giving rise to inquiries, uncertainties, deconstructions, the multiple, without which we need to hold to definitive answers or solutions. Finally, to propose a reading that can recognizing the literary text with all its multiplicity of discourse, as a space of confrontation of language, ambiguities, contradictions as well as a place of resistance and ruptures.